Virtual screening identification of novel chemical inhibitors for aberrant interactions between pathogenic mutant SOD1 and tubulin. (June 2019) - Hirayama, Kazunori; Fujiwara, Yuuki; Terada, Tohru; Shimizu, Kentaro; Wada, Keiji; Kabuta, Tomohiro
Abstract: Amyotrophic lateral sclerosis (ALS) is a lethal neurodegenerative disease caused by selective motor neuron death. Mutations in the gene encoding copper/zinc superoxide dismutase (SOD1) belong to one of the four major mutation clusters responsible for pathogenesis of ALS. Toxic gain-of-function (not loss-of-function) of SOD1 mutants causes motor neuron degeneration. Aberrant protein–protein interactions (PPI) between mutant SOD1 and other proteins are involved in this toxic gain-of-function. Therefore, PPI inhibitors of mutant SOD1 not only increase understanding of ALS pathogenesis, but can also be used as novel therapeutics for ALS. Although it is challenging to identify PPI inhibitors, prior knowledge of the binding site can increase success probability. We have previously reported that tubulin interacts with N-terminal residues 1–23 of mutant SOD1. In the present study, we performed virtual screening by docking simulation of 32, 791 compounds using this N-terminal binding site as prior knowledge. An established assay system for interaction inhibition between mutant SOD1–tubulin was used as an in-house model system to identify mutant SOD1 PPI inhibitors, with the goal of developing novel therapeutics for ALS. Consequently, five of six assay-executable compounds among top-ranked compounds during docking simulation inhibited the mutant SOD1–tubulin interaction in vitro . Binding mode analysis predicted that some inhibitors might bind the tubulin binding site of G85R SOD1 by pi electron interaction with the aromatic ring of the Trp32 residue of G85R SOD1. Our screening methods may contribute to the identification of lead compounds for treating ALS. Graphical abstract: Image 1 Highlights: Virtual screening was used to find PPI inhibitors of mutant SOD1. In-house binding site information used. PPI inhibitors were validated by pull-down assay. Applicable to screening for other mutant SOD1 interacting protein inhibitors.